Limites éticos para participação dos magistrados no espaço público democrático virtual: uma análise a partir do conceito de esfera pública de Habermas - LEÃO, Marcos Dias (2021)
This paper discusses the Ethical Limits for judges’ participation in democratic public space, both in the exercise of the jurisdictional function and outside it, considering the reality of social media and other virtual communication methods based on Habermas's ideas of discourse ethics, deliberative democracy and public space. To this end, this research uses other authors, such as Lucia Santaella, to treat the consequences generated by the dissemination of false information and its reflexes in the digital space. Based on these ideas, and the utilization of three cases, called: Magistrate X Murdered Councilwoman, Judge X Former Congressman and Roberto Barroso X Gilmar Mendes, the effectiveness of current normative instruments in the control of judges' public acts will be addressed, reinforcing the need to control their performance, given the existing limits in relation to the right to freedom of speech, including so that no crimes or conduct that undermines the legitimacy of the judiciary occurs. In addressing these questions, this research will make use of bibliographic analysis, using both the deductive and the inductive method, including some study cases. In addressing these questions, this research will make use of the bibliographic analysis, employing both the deductive and the inductive method. This study has the following research hypotheses: a) current sanctions are ineffective when applied to judges; b) the current normative instruments have not been able to limit the manifestations of judges in the virtual public space; c) the lack of control of judges' statements in the digital public space affects the legitimacy of the judiciary; and d) the influence that is exerted on society through judges may negatively reflect on the behavior of other citizens. Finally, it is important to inform that this work is constituted by three chapters. In the first one, entitled “The Ethics of Discourse and the Concept of Democratic Public Space”, some of Habermas's main ideas will be presented. In the second chapter, entitled “Virtual Realities, New Concepts of Democratic Public Space and Public Opinion”, we will seek to discuss virtual public spaces and the relationship with Habermas’ concepts. In the third chapter, called "Case Studies", it will be treated practical cases that demonstrate the need to limit the manifestations of judges in virtual public spaces.